LECTURERS' REAL CONTRIBUTIONS TO A RESILIENT INDONESIA IN THE ERA OF SOCIETY 5.0 - Umi Rusilowati; Ambar Pratiwi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
Lecturers as educators must be able to transform into agents of change, agents of analysis, and agents of control towards a strong Indonesia. All of this is in the context of advancing the public interest, educating, and advancing the life of the nation and state. Efforts are being made to implement the Tri Dharma of Higher Education, including education, research, and community service. This study aims to determine the real contribution of lecturers in realizing quality higher education outputs through the implementation of the Tri Dharma of Higher Education. This type of research is descriptive research using the survey method. From the results of this study, it can be suggested that lecturers are a key element to improve qualifications, competencies, and professionalism.